Comparison between yogurt and commercial probiotics in the duration of diarrhea in pediatric age group - Atif Amin, Baig; Aamer, Naseer; Humayun Iqbal, Khan; Mian Jawad, Ahmad; Rabia, Tariq (2017)
Objective: To compare the mean duration of diarrhea between children taking yogurt and with the group taking commercial probiotics, containing lactobacillus in acute watery diarrhea. Materials and Methods: This descriptive study was conducted in the Department of Pediatrics, Services Hospital, Lahore. The duration of this cross sectional study was 6 months, from June 2013 to November 2013. A total of 200 children suffering from acute watery diarrhea were involved in the study after the informed consent under the said hospital. Their demographic information was recorded and later divided in two groups of 100 each; group A received yogurt and group B was given commercial probiotic. The duration of diarrhea was observed in both groups. The results were compared by using independent sample t-test. Results: The average duration of diarrhea in group A, was 1.98 + 1.31 day while that in group B was 3.09 + 1.64 days. Student's t-test was applied and the difference between the two groups was found to be statistically significant (p< 0.05). Conclusions: Treatment with yogurt significantly decreases the mean duration of diarrhea as compared to probiotic among patients with acute watery diarrhea.